Large-signal vector characterization of LDMOS devices for analysis and design of broadband Doherty high-power amplifiers. Issue 7 (28th May 2019) - Cidronali, Alessandro; Collodi, Giovanni
Abstract: We present a novel broadband large-signal vector characterization technique, suitable for high-power broadband Doherty amplifiers (DPAs). It consists of characterizing the DPA three-port sub-circuit composed of the main and peak power devices that are inter-connected by the input network. We discuss a suitable way to extract the three-port X -parameters of a DPA sub-circuit, which is based on a pair of high-power Silicon Laterally Diffused MOSFETs (LDMOSs) for UHF applications. It is then applied to the analysis of a high-power broadband DPA developed on the basis of the same DPA sub-circuit. This technique permits the broadband analysis of the operation of the DPA, as well as to get insight on the load modulation for both the peak and main devices, while they mutually interact through the input network. Measurements and simulated data in the 700–960 MHz bandwidth are compared so as to demonstrate the feasibility of three-port X -parameters characterization for high-power DPAs in UHF band.